Un modelo de consenso para problemas de toma de decisiones multicriterio en grupo mediante relaciones de preferencia intervalares difusas lingüísticas - Juan Miguel Tapia García; María José del Moral; Cristóbal Tapia García; María de los Ángeles Martínez; Raúl Amor Pulido (Revista de Métodos Cuantitativos para la Economía y la Empresa, 2012)
– In some circumstances a decision maker, expert, in a group decision making problem cannot express his/her preferences with a unique linguistic fuzzy preference because he/she is dubious into some preferences. In this paper, we present a consensus model for group decision making problems with interval fuzzy preference relations. This model is based on two consensus criteria, a consensus measure and a proximity measure, and on the concept of coincidence among preferences. We compute both consensus criteria in the three representation levels of a preference relation and design an automatic feedback mechanism to guide experts in the consensus reaching process.
Keywords: C19; C63; C69; 330; group multicriteria decision making; consensus; linguistic interval fuzzy preference relations